CAMBODIA’S BL NOVEL: A STUDY ON “FORGOTTEN LOVE” - KHONGPHIANTHUM , CHANCHAI (Journal of Suan Sunandha Arts and Culture, 2023)
The Boys Love (BL) novel "Forgotten Love", published in 2022, is the work of a new author named Thuan Wuthi. The novel has several distinctive features. First, in terms of storytelling, the author uses two protagonists to narrate alternate stories through the person pronoun "I". Second, the plot is based on romantic novel and the content is new and unique especially on the issue of homosexuality and progress in science and technology. Third, the story takes place in Siam Reap Province, the city that opens to sexual diversity. Forth, the two protagonists are homosexual. The first one Puth, who is a Top while the other is Tawan, who is bottom. Fifth, the regarding the novel’s language usage, the author prefers to use English transliteration to show modernity of his novel. Sixth, based on the author’s personal preference for short films, illustrations were used in order to help tell story. Lastly, the key concept of this novel shows more openness to LGBTQ people in Khmer society. These aspects reflected in this novel has literary value and has become the identity of the author, Thuan Wuthi, who is currently featuring prominently in the Khmer society.